Teaching towards Christian environmental stewardship - to what extent are the Tbilisi Declaration objectives for environmental education relevant? - Roux, Cheryl Sheila Le (Koers, 2020)
Christians, as believers and followers of God’s word, are biblically appointed as stewards of the created biophysical world (Genesis, 1:26-31; Genesis, 2:15). This task is accomplished through practising environmental stewardship (ES). In a secular context, care for the environment is promoted through environmental education (EE). The Tbilisi Declaration (1977) articulates specific goals, objectives and principles of EE which have been followed by environmental educators for decades. This study aimed to determine to what extent the Tbilisi objectives of EE apply in the Christian context where EE is practised through educating towards ES. Research findings evidenced that apart from the five Tbilisi objectives, educating for ES employs an additional objective. This objective is the fostering of reverence for the environment which precedes the Tbilisi objective of cultivating environmental awareness. Reverence for God’s creation underlies the Christian yearning to obey, honour and bring glory to God. In the Church, educating for ES consequently should be based foremost on nurturing reverence for God’s creation. It is argued that ES will be more effective if reverence for creation is at the forefront. Onderrig jeens Christelike omgewingsrentmeesterskap – tot watter mate is die Tbilisi-verklaring se doelwitte vir omgewingsleer relevant? Opsomming Christene, as gelowiges en navolgers van God se Woord, is aangestel volgens die Bybel as rentmeesters van die geskepte biofisiese wêreld (Genesis 1:26–31; Genesis 2:15). Hierdie taak word uitgevoer deur die beoefening van omgewingsrentmeesterskap (ES). In 'n sekulêre konteks word omgewingsorg bevorder deur omgewingsleer (EE). Die Tbilisi-verklaring (1977) verwoord spesifieke mikpunte, doelwitte en beginsels van EE wat al dekades lank deur omgewingsopvoeders gevolg word. Hierdie studie se doel was om te bepaal tot watter mate die Tbilisi-doelwitte van EE in die Christelike konteks van toepassing is waar EE beoefen word met die onderrig vir ES. Bevindings uit navorsing dui daarop dat buiten die vyf Tbilisi-doelwitte, daar 'n addisionele doelwit is vir die onderrig vir ES. Hierdie doelwit is die bevordering van gesag vir die omgewing wat die Tbilisi-doelwitte vir die ontwikkeling van omgewingsbewustheid voorafgaan. Eerbied vir God se skepping lê die Christelike hunkering om God te gehoorsaam en ere aan God te betoon, ten grondslag aan. In die kerk moet die onderrig vir ES dus eerstens gebaseer wees op die kweking van eerbied vir God se skepping. Daar word geredeneer dat ES meer effektief sal wees indien eerbied vir die skepping op die voorgrond is. https://doi.org/10.19108/KOERS.85.1.2422